Produksi Spirulina platensis dalam fotobioreaktor kontinyu menggunakan media limbah cair pabrik kelapa sawit Production of Spirulina platensis in continous photobioreactor using palm oil mill effluent media - . SUHARYANTO; . TRI-PANJI; Shinta PERMATASARI; Khaswar SYAMSU (INDONESIAN OIL PALM RESEARCH INSTITUTE, 2014)
AbstractCultivation of Spirulina platensis in an abundant available and inexpensive medium such as palm oil mill effluent (POME) will produce biomass and valuable active materials at competitive price. Utilization of POME will also reduce pollution level and support cleaned production. The objectives of this research were to determine the dilution rate of S. platensis and the reduction rate of pollution level of POME on continuous photobioreactor. Preliminary research was conducted by growing S. platensis on POME medium with various concentration, namely 25%, 50%, 75%, and 90% POME on batch system. The experiment was conducted in 1.2 L capacity continous photobioreactor using medium containing a mixture of POME and synthetic medium. Feeding rate was set up at 0.05 mL/5 sec. (dilution rate of 0.03 hr -1), 0,05 mL/10 sec. (dilution rate of 0.015 hr -1), and 0.05 mL/15 sec. (dilution rate of 0.01 hr -1). For optimum dilution rate, the experiment was scaled up eight times using 10 L capacity continous photobioreactor. The results showed that optimum growth rate of S. platensis (µmax) = 0.233, was achieved using medium consisting of 90% POME and 10% synthetic medium after two weeks. Dilution rate of 0.015 hr -1 on photobioreactor was the optimum dilution rate for growth of S. platensis as well as for decreasing polution level of POME. The result of the eight-times scale up photobioreactor using flow rate of 0.4 mL/10 sec and dilution rate of 0.015 hr -1 showed that the growth of S. platensis was relatively constant as reflected by the OD value of the suspension culture and the concentration of cellular biomass. At the optimum condition, production of S. platensis biomass was 0.267g/L and pollution level was decrease 24%. The rate of outflow also resulted the constant decrease of polution level based on total carbon (TC), total dissolve solid (TDS), dissolve oxygen (DO), BOD, and COD parameters indicating that continuous photobioreactor was running at steady state.Abstrak Kultivasi S. platensis dalam media yang tersedia me-limpah dan murah seperti limbah cair pabrik kelapa sawit (LC-PKS) akan menghasilkan biomassa dan bahan aktif bernilai ekonomi tinggi dengan harga kompetitif. Pemanfaatan LC-PKS juga akan mengurangi dampak pen-cemaran lingkungan dan membantu menciptakan sistem produksi bersih. Penelitian ini bertujuan menetapkan laju dilusi optimum per-tumbuhan S. platensis dan laju penurunan tingkat cemaran LC-PKS pada fotobioreaktor sistem kontinyu. Untuk mengukur laju alir sistem kontinyu, pertama S. platensis ditumbuhkan pada media LC-PKS 25%, 50%, 75%, dan 90% dengan sistem batch. Pertum-buhan S. platensis pada fotobioreaktor sistem kontinyu kapasitas 1,2 L dirancang dengan variasi laju alir umpan berupa LC-PKS yang dicampur media sintetik pada konsentrasi optimum. Variasi laju alir pengumpanan diatur pada variasi 0.05 mL/5 detik (laju dilusi 0,03 jam-1), 0,05 mL /10 detik (laju dilusi 0,015 jam -1), dan 0,05 mL/15 detik (laju dilusi 0,01 jam-1). Pada laju alir optimum, skala percobaan diperbesar delapan kali menggunakan foto-bioreaktor berkapasitas 10 L. Hasil penelitian menunjukkan bahwa laju pertumbuhan maksimum (µ maks) adalah 0,233 jam-1 yang diperoleh dengan campuran media LC-PKS 90% dan media sintetik 10% selama dua minggu. Fotobioreaktor dengan laju dilusi 0,015 jam-1 merupakan laju alir umpan yang optimum untuk pertumbuhan S. platensis serta menghasilkan penurunan tingkat cemaran LC-PKS yang optimum. Hasil penelitian dengan perbesaran skala delapan kali menggunakan laju alir pengumpan 0,4 mL/10 detik (laju dilusi 0,015 jam-1) menunjukkan bahwa pertumbuhan S. platensis relatif konstan. Produksi biomassa sel rata-rata sebesar 0,267g/L dan kadar cemaran limbah rata-rata menurun sebesar 24%. Laju alir keluar (outflow) juga menghasilkan kadar cemaran limbah yang konstan ber-dasarkan parameter total karbon (TC), total dissolve solid (TDS), dissolve oxygen (DO), BOD, dan COD yang menunjukkan bahwa sistem fotobioreaktor kontinyu ini berjalan dengan baik.